Oncology Patients' Perspectives on Remote Patient Monitoring for COVID-19. Issue 9 (September 2021) - Daly, Bobby; Lauria, Tara S.; Holland, Jessie C.; Garcia, Jericho; Majeed, Jibran; Walters, Chasity B.; Zablocki, Melissa; Chow, Kimberly; Strachna, Olga; Giles, Caitlin E.; Kelly, Meghan F.; Housen, Ashley; et al.
Abstract : PURPOSE: Oncology patients are vulnerable to adverse outcomes associated with COVID-19, and clinical deterioration must be identified early. Several institutions launched remote patient monitoring programs (RPMPs) to care for patients with COVID-19. We describe patients' perspectives on a COVID-19 RPMP at a National Comprehensive Cancer Center. METHODS: Patients who tested positive for COVID-19 were eligible. Enrolled patients received a daily electronic COVID-19 symptom assessment, and a subset of high-risk patients also received a pulse oximeter. Monitoring was provided by a centralized team and was discontinued 14 days after a patient's positive test result and following 3 days without worsening symptoms. Patients who completed at least one assessment and exited the program were sent a patient engagement survey to evaluate the patient's experience with digital monitoring for COVID-19. RESULTS: The survey was distributed to 491 patients, and 257 responded (52% completion rate). The net promoter score was 85%. Most patients agreed that the RPMP was worthwhile, enabled better management of their COVID-19 symptoms, made them feel more connected to their healthcare team, and helped prevent emergency room visits. Identified themes regarding patient-perceived value of a RPMP included (1) security: a clinical safety net; (2) connection: a link to their clinical team during a period of isolation; and (3) empowerment: an education on the virus and symptom management. CONCLUSION: RPMPs are perceived to be of value to oncology patients with COVID-19. Policymakers should consider how these programs can be reimbursed to keep vulnerable patients at home and out of the acute care setting.